Chaplaincy in Hospice and Palliative Care. - Murphy, Karen (Jessica Kingsley Publishers, 2017)
In an increasingly secular society chaplaincy is no longer widely accepted as a necessary element of palliative care. A meditative reflection on the role played by hospice chaplains, this book argues that chaplains have a vital part to play in the care of a patient, their family, and those supporting them.